Sexuality & gender for mental health professionals : a practical guide - Richards, Christina; Barker, Meg (London : SAGE Publications, 2013)
Breaks down the complexities of sexuality and gender whilst understanding the interpretations and manifestations which can be placed on both. This title familiarises the reader with all of the common and many of the less common sexualities, genders and relationship forms, and explains experiences and issues relating to each.
Machine generated contents note: 1.Introduction -- Section 1 Gender Practices and Identities -- 2.Transgender (Trans) -- Living a Different Gender from that Assigned at Birth -- 3.Intersex/Diversity of Sexual Development (DSD) -- 4.Cisgender -- Living in the Gender Assigned at Birth -- 5.Further Genders -- Section 2 Sexuality: Practices and Identities -- 6.Bondage and Discipline, Dominance and Submission, and Sadomasochism (BDSM)/Kink -- 7.Asexuality -- 8.Bisexuality -- 9.Lesbian and Gay Sexuality -- 10.Heterosexuality -- 11.Cross-dressing -- 12.Further Sexualities -- Section 3 Relationship Structures -- 13.Monogamy -- 14.Non-monogamy.
Includes bibliographical references and index.
Keywords: Sex (Psychology); Gender identity; Sex customs -- Psychological aspects; Sex (Psychology)